تطبيق برنامج منظمة الأسد في ترقيّة مهارة الكلام في معهد عدلانية باسمان الغربيّة - Difa Arthyla Sebayang; Albaihaqi Anas (Lembaga Yasin AlSys, 2026)
Although the development of Arabic speaking skills (maharah al kalam) has attracted increasing attention in Arabic language education, studies specifically examining the role of student organizations in fostering speaking proficiency within Islamic boarding schools remain limited. This study aims to analyze the implementation of the Al Asad Organization Program in developing students’ Arabic speaking skills at Adlaniyah Modern Islamic Boarding School. A qualitative approach with a case study design was employed. The participants consisted of the organization supervisor, student organization administrators, and selected students chosen through purposive sampling. Data were collected through observation, semi structured interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal that the Al Asad Organization successfully develops students’ speaking skills through integrated language programs, including daily vocabulary enrichment, muhadatsah (conversation), muhadarah (speech practice), language supervision, and periodic evaluation. The success of the program is supported by strong institutional commitment, active participation of students, competent supervisors, and the establishment of a consistent Arabic speaking environment. However, limited vocabulary mastery, low self confidence, and varying language abilities remain challenges. These findings contribute to the development of communicative language learning and the concept of bi’ah lughawiyyah in Islamic boarding schools by demonstrating the strategic role of student organizations in creating sustainable language practices. The study concludes that student organizations are an effective medium for strengthening Arabic communicative competence and recommends broader institutional support for language based student organizations.